KOTA TUA SEBAGAI RUANG KREASI DIGITAL: EKSPLORASI KOTA TUA SEBAGAI ARENA PRODUKSI KONTEN BAGI KONTEN KREATOR - Dinda Fatimah Zahra; Nisa Haniatus Syuhada; Nabil Pratama Nusantara; Naeni Amanulloh (UNIVERSITAS SEBELAS MARET (UNS), 2024)
Kota Tua Jakarta plays a crucial role as a center of historical and architectural wealth, serving as a primary source of inspiration for content creators in the digital era. This study aims to gain a deep understanding of the selection and digital representation by content creators in Kota Tua Jakarta. The research employs a qualitative method with a descriptive-analytical approach. Utilizing Bourdieu's theoretical framework, the study examines cultural capital, social structures, and symbolic practices shaping the digital creativity arena in Mangga Besar, Taman Sari District, West Jakarta, Special Capital Region of Jakarta. It explores various types of content creators, including vloggers, bloggers, podcasters, and digital artists. The findings reveal that Kota Tua Jakarta is not merely a visual backdrop but also provides rich historical narratives adapted by content creators to craft unique digital experiences. This research contributes to understanding how Kota Tua Jakarta functions as a dynamic arena for digital creativity. By enhancing appreciation for history and cultural richness, the study aspires to strengthen the global image of Kota Tua Jakarta as an inspiring historical destination.